ANALISIS KEMAMPUAN BERPIKIR METAFORA PADA POKOK BAHASAN BARISAN DAN DERET - Sri Yelinda Tama; Sumarno Ismail; Franky A. Oroh; Abas Kaluku (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2019)
This study aims to describe students' metaphorical thinking ability on the subject sequences and series. The research was conducted using a descriptive method involving 32 students of SMA Negeri 1 Gorontalo Utara as research subjects. The instrument used was an essay test to obtain data on metaphorical thinking skills and interviews to complement and strengthen the information that came from giving tests on the subject sequence and series. The data analysis technique used is in the form of a percentage with standard deviation categorization criteria, to determine the level of students' metaphorical thinking ability. The results of the analysis showed that the students' metaphorical thinking ability in the subject sequences and series were in the medium category.